The “Pacto de Ochomogo”: Historical metaphor in the construction of Costa Rican modernity - Hernández-Castro, Gustavo (2022)
The authors analyze the “Pacto de Ochomogo” (Ochomogo Agreement) -1948 Civil War in Costa Rica- from the point of view of witnesses of this historical event and the different historiographical stories. Their hypothesis is that the ”Pacto de Ochomogo” became a historical metaphor in Costa Rican modernity. In other words, XXIth Costa Rica is the result of a historical event that, according to the winners of the war, it’s an agreement that never existed (a written document). Through the method of hermeneutics, the authors examine intratexts related to people who participated in the historical event and historiographic data collected by different researchers.